2017
DOI: 10.1007/s00168-017-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration externalities, competition and productivity: empirical evidence from firms located in Ukraine

Abstract: This paper studies role of agglomeration externalities and market structure in determination of total factor productivity (TFP) of Ukrainian firms, having controlled for individual firm characteristics. We use micro-level data for manufacturing and service sectors in years 2005 and 2013. Our empirical results confirm the importance of various agglomeration externalities as well as competition in determination of TFP of Ukrainian firms. In addition, we find the statistically significant link between the total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This is consistent with Porter's theory that competition in similar industries will increase firm productivity compared to a monopoly environment. The positive effect of the competition is also in line with Badr et al (2019), Khoirunurrofik (2018), Cieślik et al (2017), Wixe (2015), and Widodo et al (2014).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This is consistent with Porter's theory that competition in similar industries will increase firm productivity compared to a monopoly environment. The positive effect of the competition is also in line with Badr et al (2019), Khoirunurrofik (2018), Cieślik et al (2017), Wixe (2015), and Widodo et al (2014).…”
Section: Resultssupporting
confidence: 54%
“…Research by Malmberg et al (2000), Antonietti & Cainelli (2011), Li et al (2012), Badr et al (2019), Cheng & Jin (2020) concluded that both specialization and diversification have a positive impact on firm performance. Meanwhile, research by Widodo et al (2014), Galliano et al (2015), Cieślik et al (2017), Wardani & Yudhistira (2020) concluded that only specialization has a positive effect, while diversification harms firm performance. Batisse (2002) found that specialization harms regional growth, while diversification has a positive impact.…”
Section: Introductionmentioning
confidence: 99%
“…Their characteristics determine their performance and their capacity of absorption of benefits at the industrial or regional level of agglomeration externalities. The existent literature about agglomeration economies has mainly focused on agglomeration economies derived in firms in general (Cie slik et al, 2018;de Groot et al, 2016;Melo et al, 2009) and some studies focus on the effect of these general agglomeration economies on firms by size (Humphrey, 1995;Li et al, 2012;Rosenthal & Strange, 2010;Sweeney & Feser, 1998). The effect of firm-specific-derived agglomeration economies has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of industry [20], region, and country [12], scholars point out the contribution of geographic clusters and Research & Development clusters to industrial and national economic growth from the angle of spatial externalities of cluster economies. In particular, compared with the impact of intra-industry clusters, the upstream industry has a more obvious effect on the improvement of enterprise productivity.…”
Section: Cross-regional Innovation Clustersmentioning
confidence: 99%